2020
DOI: 10.3390/cancers12041007
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Genetic Susceptibility to Melanoma by Gene Panel Testing: Potential Pathogenic Variants in ACD, ATM, BAP1, and POT1

Abstract: The contribution of recently established or candidate susceptibility genes to melanoma missing heritability has yet to be determined. Multigene panel testing could increase diagnostic yield and better define the role of candidate genes. We characterized 273 CDKN2A/ARF and CDK4-negative probands through a custom-designed targeted gene panel that included CDKN2A/ARF, CDK4, ACD, BAP1, MITF, POT1, TERF2IP, ATM, and PALB2. Co-segregation, loss of heterozygosity (LOH)/protein expression analysis, and splicing charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 70 publications
4
26
0
1
Order By: Relevance
“…A higher prevalence of mutations in ACD , TERF2IP , and POT1 was identified in 12/132 (9.1%) high-risk CDKN2A / CDK4 / TERT / BAP1 wild-type European and Australian patients with multiple melanoma (≥3) [ 44 ]. A higher prevalence of germline mutations in BAP1 (not identified in our patients) and POT1 was also reported in a recent study by Pastorino and colleagues who identified seven carriers (2.6%) of mutations in each of these two genes among 273 Italian melanoma patients [ 45 ]. The enrollment of 22 melanoma patients with atypical Spitz nevi with relatives developing BAP1 -related tumors can explain an increased prevalence of BAP1 mutation carriers in this Italian study.…”
Section: Discussionsupporting
confidence: 86%
“…A higher prevalence of mutations in ACD , TERF2IP , and POT1 was identified in 12/132 (9.1%) high-risk CDKN2A / CDK4 / TERT / BAP1 wild-type European and Australian patients with multiple melanoma (≥3) [ 44 ]. A higher prevalence of germline mutations in BAP1 (not identified in our patients) and POT1 was also reported in a recent study by Pastorino and colleagues who identified seven carriers (2.6%) of mutations in each of these two genes among 273 Italian melanoma patients [ 45 ]. The enrollment of 22 melanoma patients with atypical Spitz nevi with relatives developing BAP1 -related tumors can explain an increased prevalence of BAP1 mutation carriers in this Italian study.…”
Section: Discussionsupporting
confidence: 86%
“…These genes mainly encode for tumor suppressor proteins involved in cell cycle regulation, apoptosis and DNA repair pathways; being involved in cancer development, they are called cancer susceptibility genes ( 113 ). The identification of these genes have paved the way for the development of targeted therapeutic approaches as well as for cancer prevention and surveillance ( 114 , 115 ). The most common inherited cancer risk factor associated with MPM is the aberration of BRCA1 Associated Protein 1 ( BAP1 ), a deubiquitinating enzyme located on chromosome 3p21.1 acting as tumor suppressor gene ( 116 , 117 ).…”
Section: Genetic Alterations Predisposing To Mesotheliomamentioning
confidence: 99%
“…These alterations are more frequently detected in young adults with MPM: 4% in patients older than 75 years and 20% in the ones of 55 years of age or younger ( 121 ). Among the three histotypes of MPM, such as epithelioid, sarcomatoid, and biphasic, BAP1-germline mutations are found more frequently in the epithelioid and this correlates with a better prognosis ( 113 , 115 ).…”
Section: Genetic Alterations Predisposing To Mesotheliomamentioning
confidence: 99%
“…ACD loss of function (LOF) mutations predispose to melanoma and a broader spectrum of cancers [ 59 ]. Despite the fact that no RCCs were reported in ACD carriers to date [ 59 , 60 , 61 ], a meta-analysis suggested that individuals with an inherited predisposition to longer telomere length are at increased risk of developing renal cell carcinoma [ 62 ]. Two other cases respectively harbored a novel 14-base-pair deletion (c.2228_2240del p.(Q743fs)) and a rare missense VUS (rs1588304158) in TSC1 .…”
Section: Resultsmentioning
confidence: 99%